Gambaran Upaya Promosi Kesehatan 3M Plus Di Masyarakat Dalam Pencegahan DBD Di Kelurahan Karet Kuningan Jakarta Selatan Tahun 2023 - Sekar Retno Pradini; Suraya, Izza; A’yunin, Elia Nur (LPPM Sekolah Tinggi Ilmu Kesehatan Pekanbaru Medical Center, 2023)
DHF is still a health problem that is of great concern in Indonesia. In 2020, in Karet Kuningan Village alone there were 10 cases of dengue fever, and 2 cases of death due to dengue fever. According to data from jumantik cadres, in 2021 the number of dengue fever cases has decreased to 7 cases. The lack of public awareness in preventing dengue fever through 3M Plus activities is the cause of dengue fever continuing to occur every year. The aim of this research is to find out an overview of 3M Plus health promotion efforts in the community in preventing dengue fever in Karet Kuningan Village, South Jakarta in 2023. The time to be implemented is from June to August 2023. In this research the researcher is interested in making the topic an overview of 3M Plus' health promotion efforts in community in preventing dengue fever in Karet Kuningan Village, South Jakarta in 2023. This research uses qualitative research which is complemented by quantitative. This research consisted of 102 respondents from the RT.017 and RT communities. 018 in Karet Kuningan Village, South Jakarta. The results of in-depth interviews stated that there were health promotion activities carried out in the Karet Kuningan Subdistrict Area, South Jakarta, namely the One House One Jumantik Movement (G1R1J). Univariate results showed knowledge (92.2%), attitudes (52%), and poor behavior (56.9%). Therefore, the Karet Kuningan sub-district area, South Jakarta, must increase health promotion and increase public awareness of efforts to prevent dengue fever.